IMPLEMENTING DRILL METHOD TO INCREASE MATHEMATICS LEARNING OUTCOMES OF GRADE II ELEMENTARY STUDENTS ON MULTIPLICATION MATERIAL - Naila Kurnia Restu; Siti Ruqoyyah; Uke Viani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research was triggered by the low level of the learning outcomes on the mathematics learning at primary schools. It was also based on the results of observation finding that there were problems constraining the success of learning mathematics at primary schools. One of which was the students’ low achievement and the mathematics learning which were less attractive to students. This research aimed to improve the students’ mathematics learning outcomes on multiplication material by implementing drill method. This research was classroom action research in which the researchers compared the increase of students’ learning outcomes before and after the implementation of drill method in two cycles. This research was conducted in SDN Cibeber 1 at Kecamatan Cimahi Selatan, Kota Cimahi. The results of this study indicated that the students’ mathematics learning outcomes on multiplication material increased as much as 52.2% after the implementation of drill method. Thus, it could be concluded that the drill method could increase the mathematics learning outcomes of grade II elementary students in the multiplication material.